2019
DOI: 10.1038/s41467-019-11374-8
|View full text |Cite
|
Sign up to set email alerts
|

The Rad51 paralogs facilitate a novel DNA strand specific damage tolerance pathway

Abstract: Accurate DNA replication is essential for genomic stability and cancer prevention. Homologous recombination is important for high-fidelity DNA damage tolerance during replication. How the homologous recombination machinery is recruited to replication intermediates is unknown. Here, we provide evidence that a Rad51 paralog-containing complex, the budding yeast Shu complex, directly recognizes and enables tolerance of predominantly lagging strand abasic sites. We show that the Shu complex becomes chromatin assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 53 publications
7
38
0
Order By: Relevance
“…We can only speculate that either Pol α maybe somehow inhibited at bulky lesions in mammalian cells, or that PrimPol might have additional roles in promoting HR at gaps, for example by interacting with DNA repair factors or due to its preference to synthesize DNA primers 12 . Interestingly, recent work also suggests that different DNA damage tolerance pathways may be active at the leading versus the lagging strand in budding yeast 44 . It will be important, if challenging, to further investigate how re-priming via PrimPol specifically promotes HR-dependent gap repair.…”
Section: Discussionmentioning
confidence: 99%
“…We can only speculate that either Pol α maybe somehow inhibited at bulky lesions in mammalian cells, or that PrimPol might have additional roles in promoting HR at gaps, for example by interacting with DNA repair factors or due to its preference to synthesize DNA primers 12 . Interestingly, recent work also suggests that different DNA damage tolerance pathways may be active at the leading versus the lagging strand in budding yeast 44 . It will be important, if challenging, to further investigate how re-priming via PrimPol specifically promotes HR-dependent gap repair.…”
Section: Discussionmentioning
confidence: 99%
“…During evolution, duplications of the Rad51 gene have resulted in so-called Rad51 paralogues [ 3 ], a set of factors that are found in variable numbers in different organisms and whose spectrum of roles remain somewhat undefined, at least in part because they can belong to a number of protein complexes. Nonetheless, Rad51 paralogues have been implicated in directly modulating HR, acting on Rad51 HR intermediates [ 4 6 ], and in wider repair activities for cell cycle progression [ 7 , 8 ]. HR reactions mediated by Rad51 [ 9 12 ] and modulated by the Rad51 paralogues [ 13 ] are also required for resolving DNA replication impediments, by promoting protection and restart of stalled replication forks during replication stress.…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, with Pol α constantly repriming on the lagging strand and possibly also the leading strand, one would expect at most half of gap- and RAD51 foci formation to be PrimPol-dependent. Recent work has suggested that in budding yeast, different pathways act on the leading and lagging strands 40 it will be interesting to investigate whether only re-priming via PrimPol promotes HR-dependent gap repair, possibly due to PrimPol’s preference to synthesise DNA primers.…”
Section: Discussionmentioning
confidence: 99%